Nilai-Nilai Pendidikan Karakter Menurut K.H. Bisri Mustofa Dalam Tafsir Al-Ibriz - Mahbub, Ali; Siregar, Maragustam; Hasyim, A. Dardiri (Universitas Islam Negeri (UIN) Salatiga, 2024)
This study aims to analyze KH Bisri Mustofa's thoughts on character education values and assess the relevance of his ideas in Indonesia. The research methodology employed is library research, specifically a descriptive approach. The primary source of data for this study is KH Bisri Mustofa's book, Tafsir Al-Ibriz. Data collection techniques include documentation and interviews, with data analysis using triangulation. The research findings present the values of character education according to KH. Bisri Mustofa in the Ibiz Tafsir Book, which include nationalism, tolerance, justice, honesty, love of knowledge, anti-corruption, and character education. Bisri Musthofa's relevance in Indonesia persists due to its emphasis on nationalism and tolerance. The character of nationalism is crucial for Indonesia to avoid division, given its long history of struggle for independence. Additionally, fostering a society that respects and appreciates progress through tolerance can lead to a peaceful and harmonious life. A society that values honesty will be closer, and a society that prioritizes science will become educated and advanced. Anti-money politics is an important character value, especially during elections, which can be problematic for democracy. A fair and dignified election process with an anti-money politics character can prevent fraudulent violations. All of these values are still relevant and can help address the decline of commendable character in society.